Citrus Fruit Morphology in Gede Market Solo as a Learning Resource for Species Diversity - Pangestu, Prestiani Yulia; Hanik, Nur Rokhimah (Jurnal Biologi Tropis, 2025)
Biology learning at the high school level requires teaching resources that can connect theoretical concepts with real phenomena so that students gain more meaningful learning experiences. This study aimed to identify the morphological diversity of citrus fruits sold at Gede Market Solo and assess their potential as a locally based biology learning resource. Data collection was carried out through direct observation by randomly selecting 14 types of citrus fruits from several vendors, documenting their morphological characteristics through photographs, and conducting brief interviews to obtain additional information related to each fruit type. The data were then descriptively analyzed based on several morphological indicators, namely, skin color, skin texture, skin thickness, fruit diameter, fruit shape, and flesh color. The results showed that Pasar Gede Solo contains a highly diverse range of citrus fruits with clear morphological variations across categories and species. These variations enable citrus fruits to be used as real objects in identification and classification activities within biodiversity lessons, allowing students to engage in direct observation and understand concepts more contextually. The diversity of citrus fruits also provides opportunities for students to practice scientific process skills through activities such as observation, recording, comparison, and analysis of morphological features. These findings demonstrate that utilizing locally available citrus fruits can enrich biology learning, strengthen conceptual understanding, foster critical thinking, and cultivate students’ awareness of local biodiversity. This study explicitly highlights the use of morphological diversity of citrus fruits in a traditional market as a contextual and locally based biology learning resource, which has rarely been explored in previous biodiversity learning studies.